2007
DOI: 10.1248/cpb.55.944
|View full text |Cite
|
Sign up to set email alerts
|

Development of Tubulin-Polymerization Inhibitors Based on the Thalidomide Skeleton

Abstract: We synthesized a series of compounds based on the potent tubulin-polymerization inhibitor 5-hydroxy-2-(2,6-diisopropylphenyl)-1H-isoindole-1,3-dione [5HPP-33 (3)], which is structurally derived from thalidomide (1), and investigated their inhibitory effects on tubulin polymerization. Direct interaction between 5HPP-33 (3) and a a,b b-tubulin heterodimer protein was demonstrated by means of a surface plasmon resonance study.Key words thalidomide; phthalimide skeleton; tubulin polymerization inhibitor; surface p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 22 publications
3
16
0
Order By: Relevance
“…Our findings suggest that 5HPP-33 5 binds only to free a,b-tubulin heterodimer protein to inhibit tubulin polymerization, but not to polymerized tubulin. In fact, studies using surface plasmon resonance (SPR) measurement techniques suggested that 5HPP-33 5 binds directly to a,b-tubulin heterodimer protein with the calculated association constant of 4.5610 6 M -1 under our experimental conditions [32]. The calculated value is in good agreement with the IC 50 value of 5HPP-33 5 for inhibition (6.9 lM) of tubulin polymerization.…”
Section: Mode Of Tubulin Polymerization-inhibition By 5hpp-33supporting
confidence: 78%
See 1 more Smart Citation
“…Our findings suggest that 5HPP-33 5 binds only to free a,b-tubulin heterodimer protein to inhibit tubulin polymerization, but not to polymerized tubulin. In fact, studies using surface plasmon resonance (SPR) measurement techniques suggested that 5HPP-33 5 binds directly to a,b-tubulin heterodimer protein with the calculated association constant of 4.5610 6 M -1 under our experimental conditions [32]. The calculated value is in good agreement with the IC 50 value of 5HPP-33 5 for inhibition (6.9 lM) of tubulin polymerization.…”
Section: Mode Of Tubulin Polymerization-inhibition By 5hpp-33supporting
confidence: 78%
“…Investigations using porcine tubulin fraction revealed that 5-OH-thalidomide 9 and N-OH-thalidomide 10 possess moderate tubulin polymerizationinhibiting activity (Fig. 5A) [30,32].…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, nucleophilic attack of ethylenediamine in methanol toward FSA (1) occurred selectively at the 11-position to give DAFSA (9), which was used as a substrate for coupling with Affi-Gel 10 (Chart 2). As expected, DAFSA (9) showed only very weak anti-proliferative activity toward HL-60 cells (IC 50 value of Ͼ100 mM; growth was inhibited by only 24% at 100 mM concentration) and moderate anti-angiogenic activity measured by assay of HUVEC tube formation-inhibitory activity (Table 1), indicating the suitability of DAFSA-Gel as a negative control gel.…”
Section: Identification Of Binding Proteins Of Fusarielin a As Actin supporting
confidence: 70%
“…All of the prepared compounds were initially screened at 30 lM concentration by means of TPI assay, 31 used in identifying tubulin polymerization inhibitors. Secondly, the tumor cell growth-inhibitory activity of the synthesized compounds towards human breast cancer cell line (MCF-7) was evaluated.…”
Section: Tubulin Polymerization-inhibitory Activity and Tumor Cell Grmentioning
confidence: 99%
“…31 Briefly, microtubule protein was prepared from porcine brain by several cycles of assembly-disassembly, as described. 32 Tubulin solution was prepared at a concentration of 1.8-2.0 mg/ml.…”
Section: Tubulin Polymerization Inhibition (Tpi) Assaymentioning
confidence: 99%